Developing the quality of palm oil with herbal extracts - Jiyipong, Patinya; Yossaksri, Janchay (Bulletin of Applied Sciences, 2022)
The purpose of this study was to produce palm oil with antioxidants for reduced rancidity in fried food products. The three types of herbal; ginger, turmeric and finger root were used in this experiment. The higher concentration of herbal extracts, the higher of total phenolic contents (TPC). The palm oil samples were mixed with 2%, 4%, and 6% of herbal powder and were mixed with 200, 400 and 600 mg./kg. of herbal extracts by ethanol. The quality determination of palm oil by using Peroxide value (P.V.) and Acid value (A.V.). The selected formulations of palm oil with herbal powder were 2% ginger, 4% turmeric and 2% finger root, their P.V. were 5.50 0.22 6.20 0.04 6.18 0.08 meq/kg, respectively. While the palm oil with herbal extracts were ginger 200, turmeric 400 and finger root 400 mg./ kg, their PV. were 4.48 0.03 5.60 0.02 5.82 0.01 meg/kg., respectively. All samples also had A.V. lower than 0.6 in mg./g. The quality determination of fried palm oil, the P.V. of palm oil with ginger extract was lower than that of turmeric and finger root extract. For fried chips sensory testing by 30 panelists, they accepted chips that fried in palm oil with ginger extract, finger root extract, turmeric extract and control, respectively. The palm oil with herbal extracts had stored at least one year shelf life.